2022
DOI: 10.1136/bmjopen-2021-057994
|View full text |Cite
|
Sign up to set email alerts
|

Using community influencer groups to address COVID-19 misinformation and vaccine hesitancy in Uganda: a protocol for a prospective quasi-experimental study

Abstract: IntroductionCoronovirus disease 2019 (COVID-19) misinformation has been reported globally and locally. This has the potential to influence public risk perception and reduce the acceptance of the COVID-19 vaccine. This study aims to determine the prevalence of COVID-19 misinformation and vaccine hesitancy in Buikwe district. The study will also pilot a social mobilisation intervention using community influencers and determine its effect on COVID-19 misinformation and vaccine hesitancy.Methods and analysisThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Younger adults likely have more dynamic social networks and may be more amenable to peer effects regarding new health behaviors like COVID-19 vaccination. 27 , 28 Our results suggest peer-focused communication efforts could help boost vaccine uptake in this age group. While causal mechanisms require further investigation, these correlational findings already point to an important phenomenon with pragmatic implications that should not be disregarded due to design constraints.…”
Section: Discussionmentioning
confidence: 72%
“…Younger adults likely have more dynamic social networks and may be more amenable to peer effects regarding new health behaviors like COVID-19 vaccination. 27 , 28 Our results suggest peer-focused communication efforts could help boost vaccine uptake in this age group. While causal mechanisms require further investigation, these correlational findings already point to an important phenomenon with pragmatic implications that should not be disregarded due to design constraints.…”
Section: Discussionmentioning
confidence: 72%
“…this misinformation related to COVID-19 in Uganda have been reported in many media outlets from the onset of the pandemic [ 6 ]. However, experts suggested that regular communications, providing updates on the status of the pandemic in-country to encourage government agencies and Task forces to use mainstream and social media to inform and provide guidance on COVID-19 situational analysis at international, national, and local levels were critical [ 8 ]. This approach was important because communities needed not to be fed on fake news and inaccurate information because these hampered progress in the control of the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de alguns artigos apontarem a relevância de influenciadores digitais para a propagação de mensagens pró-vacina nas mídias sociais (MALIK; AWAN; SALEEM, 2020;BONNEVIE et al, 2021;DUCK et al, 2022;SSANYU et al, 2022) O Facebook é a rede social mais usada para consumo de informações no Brasil (NEWMAN et al, 2021) e, atualmente, conta com mais de 150 milhões de usuários no país (STATISTA, 2022a). Dado seu alcance no cenário brasileiro, essa rede social foi utilizada pela população para tratar de assuntos relativos à vacina contra a Covid-19 (SILVA; PIRES; PAIVA, 2022).…”
Section: Introductionunclassified